AF Fashion / Nur Aliah Fatihah Mohd Sukri - Nur Aliah Fatihah, Mohd Sukri (2020)
AF FASHION offers clothe shop product and service for customers, and provides a hoodie with a lot of uniqueness that given high satisfaction of customer. Besides that, our customers identified from various groups and area (some is like fashionable, some is really need it but don’t have enough money and some do not have a lot of money but want to have a hoodie) who want consume product with affordable price of product WM hoodie. The high quality fabric and materials that give the benefits to our customers also offers by AF FASHION. We design this hoodie for the benefit and satisfaction of customers, so our customers will feel comfortable using our brands hoodie. Our concepts is simple but nice. Besides that, our shop is located at Kuala Lumpur which the location was known to be the industrial and textile city of Kuala Lumpur. The 2 in one jackets and back to back hoodie market are still unknown in Malaysian fashion industry. So, we decided to bring this back to back hoodie fashion Malaysian market. We also targeting experienced and busiest workers because we have delivery services of our product to customer home without any postage and also online sales. AF FASHION business can seen an explosion of growth over the year. For examples, across Kuala Lumpur and Selangor, there are many fashionable people because they live in the up-to-date area, it cause demand of hoodie is rise. While there are currently five business like us in Kuala Lumpur and Selangor, but only AF FASHION business have unique hoodie and provide special delivery service. Emphasize the price and the quality of our products and service is the AF FASHION marketing strategy. The affordable price also has offered by AF FASHION because a lot of people very low income and poor family, for examples like at the Genting Highlands and Cameron Highlands that needs the hoodie. The management of AF FASHION consists of 2 lead workers is Adam and Fatihah. Our workers has extensive experiences in business, accounting and only Fatihah has experiences work in fashion company, Fashion Valet. Two partners will take role responsibility together instead different duties and portfolio of partners. We have service and products commitments plan to aggressively build our brand through signboard, ads (Instagram, television, Twitter and Facebook) and newspaper. The AF FASHION company will provide is sure to appeal to customers, throughout the area. In future, we believe that AF FASHION will be able to complete with the other hoodie brand either locally or internationally.